(3GdYQH h KhQI GdeYdheGJ (B/s - (3GdNhdj, CSGeIs; (3eQcR OQGSGJ GdhMOI GdYQHjIs ((3dHfGf (B:s (3eQcR OQGSGJ GdhMOI GdYQHjI ,s, 2005)
(3JcfhdhLjG GdeYdheGJ(B- (3GdHdOGf GdYQHjI(B- (3GdJLGQI GdEdcJQhfjI(B- (3GdHdOGf GdYQHjI (B- (3GdEfJQfJs
Keywords: (3GdCfJQfJs; (3GdHdOGf GdYQHjIs; (3JcfhdhLjG GdeYdheGJs